2001
DOI: 10.1099/00221287-147-11-3165
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal infection of BALB/c mice with Yersinia enterocolitica O9 causes major modifications in phenotype and functions of spleen cells

Abstract: INTRODUCTIONYersinia enterocolitica is a common cause of intestinal infections in humans (Cover & Aber, 1989 ;Bottone, 1997). Extraintestinal and systemic infections are most often caused by strains belonging to so-called highvirulence serotypes, such as serotype O8 (Heesemann et al., 1993), although low-virulence serotypes, such as O3 and O9, may occasionally cause bactaeremia in patients with iron overload or other underlying diseases (Rabson et al., 1975 ;Bouza et al., 1980). The presence of a 70 kb plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…It is believed that in murine yersiniosis, protective-cell-associated defense mechanisms comprise macrophages/NK cells, which become activated via T helper cells (CD4) producing significant amounts of IFN-␥ (40,41). In rainbow trout lymphoid organs, we found high expression of both IFN-␥ and TNF-␣ genes in nonimmunized Y. ruckeri-infected fish and moderate regulation in vaccinated fish, especially on day 3 p.i.…”
Section: Discussionmentioning
confidence: 72%
“…It is believed that in murine yersiniosis, protective-cell-associated defense mechanisms comprise macrophages/NK cells, which become activated via T helper cells (CD4) producing significant amounts of IFN-␥ (40,41). In rainbow trout lymphoid organs, we found high expression of both IFN-␥ and TNF-␣ genes in nonimmunized Y. ruckeri-infected fish and moderate regulation in vaccinated fish, especially on day 3 p.i.…”
Section: Discussionmentioning
confidence: 72%
“…Infection with IP383 is able to induce macrophage activation linked to an inhibition of the capacity of splenocytes to proliferate in response to both B‐cell and T‐cell mitogens [9]. To assess if live Y. enterocolitica were necessary for the observed suppression of ex vivo lymphoproliferation, the responses of spleen cells from 10‐day‐infected mice, HKY‐treated mice and untreated controls were compared.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that low‐virulence Y. enterocolitica strains possess immunomodulatory properties [7–9]. Interestingly, experimental infection with IP383, a pYV‐bearing strain belonging to the low‐virulence serotype O9, confers on BALB/c mice significant resistance levels against transplantation of the syngeneic lymphoma LSTRA or challenge with a lethal dose of the intracellular pathogen Listeria monocytogenes [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenteric lymph nodes become amplified and the focal area of necrosis exhibits leukocytes infiltration Bliska, 2005, Ruckdeschel et al, 1996). Studies of the intestine of Y. enterocolitica O9 infected BALB/c mice indicates that the infected mice exhibit splenomegaly, and development of CD3 + total T cells, CD4 + Th cells, CD8 + Tc cells, and CD11b + phagocytic cells (Ruiz-Bravo et al, 2001). The infection also causes the impaired response and proliferation of normal splenocytes against the mitogens, which in turn promotes the inhibition of lymphocyte responding to mitogens.…”
Section: Interplay Of the Yersinia With Gut System And Tlrsmentioning
confidence: 99%